Sediment dynamics and implications for management: State of the science from long‐term research in the Chesapeake Bay watershed, USA. (21st June 2020) - Noe, Gregory B.; Cashman, Matthew J.; Skalak, Katie; Gellis, Allen; Hopkins, Kristina G.; Moyer, Doug; Webber, James; Benthem, Adam; Maloney, Kelly; Brakebill, John; Sekellick, Andrew; Langland, Mike; et al.
Abstract: This review aims to synthesize the current knowledge of sediment dynamics using insights from long‐term research conducted in the watershed draining to the Chesapeake Bay, the largest estuary in the U.S., to inform management actions to restore the estuary and its watershed. The sediment dynamics of the Chesapeake are typical of many impaired watersheds and estuaries around the world, and this synthesis is intended to be relevant and transferable to other sediment‐impaired systems. The watershed's sediment sources, transport, delivery, and impacts are discussed with implications for effectively implementing best management practices (BMPs) to mitigate sediment issues. This synthesis revealed three key issues to consider when planning actions to reduce sediment loading: Scale, time, and land use. Geology and historical land use generated a template that current land use and climate, in addition to management, are acting upon to control sediment delivery. Important sediment sources in the Chesapeake include the Piedmont physiographic region, urban, and agricultural land use, and streambank erosion of headwater streams, whereas floodplain trapping is important along larger streams and rivers. Implementation of BMPs is widespread and is predicted to lead to decreased sediment loading; however, reworking of legacy sediment stored in stream valleys, with potentially long residence times in storage, can delay and complicate detection of the effects of BMPs on sediment loads. In conclusion, the improved understanding of sediment sources, storage areas, and transport lag times reviewed here can help target choices of BMP types and locations to better manage sediment problems—for both local streams and receiving waters. This article is categorized under: Science of Water > Water Quality Water and Life > Stresses and Pressures on Ecosystems Water and Life > Conservation, Management, and Awareness Abstract : Diverse best management practices (BMPs) are implemented across watersheds to reduce downstream sediment loading by addressing agricultural, urban, and streambank sources and sediment storage zones. A better understanding of sediment sources, transport, delivery, and impacts will help target these management actions.